Implementasi Algoritma First Come First Serve (FCFS) pada Sistem Manajemen Pengaduan Online APTIKA - Rizka Annisa; Anita Ahmad Kasim (Jurnal Algoritma, 2026)
The high demand for digital services, which is not yet supported by an integrated complaint management system, has led to low transparency and slow handling of reports. This study developed a web- and mobile-based complaint management system by implementing the First Come First Serve (FCFS) algorithm for queue management. The research method uses a mixed method with black-box functional testing and performance evaluation through a pre-test and post-test scheme analyzed using the Paired Sample T-Test. The results show an acceleration in resolution time across all service categories with efficiency levels ranging from 60.9% to 91.3%. Statistically, the significance value (p-value < 0.05) proves an improvement in performance compared to the manual method. The contribution of this research is the integration of FCFS and Role-Based Access Control (RBAC) into a structured and efficient multi-service-based government complaint system. The limitations of this study lie in the use of simulation data in the post-test as well as pre-test data that is estimative with a limited sample, so the results do not yet fully represent real operational conditions and still require further testing.